2019
DOI: 10.1016/j.neo.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Eaf1 Induces Murine Prostatic Intraepithelial Neoplasia in Mice

Abstract: ELL-associated factor 1 is a transcription elongation factor that shares significant homology and functional similarity to the androgen-responsive prostate tumor suppressor ELL-associated factor 2. EAF2 is frequently down-regulated in advanced prostate cancer and Eaf2 deletion in the mouse induced the development of murine prostatic intraepithelial neoplasia. Here we show that similar to EAF2, EAF1 is frequently down-regulated in advanced prostate cancer. Co-downregulation of EAF1 and EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It has previously been suggested that EAF2 serves as a tumor suppressor in prostate cancer [27,28]. EAF2 is frequently down-regulated in advanced prostate cancer and EAF2 deletion in the mouse induced the development of murine prostatic intraepithelial neoplasia [29,30]. Furthermore, one study demonstrated that EAF2 might inhibit the invasion, migration, and angiogenesis of colorectal cancer cells, and play a cancer suppressive and protective role in the occurrence and development of colorectal cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that EAF2 serves as a tumor suppressor in prostate cancer [27,28]. EAF2 is frequently down-regulated in advanced prostate cancer and EAF2 deletion in the mouse induced the development of murine prostatic intraepithelial neoplasia [29,30]. Furthermore, one study demonstrated that EAF2 might inhibit the invasion, migration, and angiogenesis of colorectal cancer cells, and play a cancer suppressive and protective role in the occurrence and development of colorectal cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…KIF13B interacts with the tubulin VEGFR2, and KIF13B depletion prevents VEGF-mediated neo-vascularization and endothelial migration( Yamada et al, 2014 ). EAF2 is a potential tumor suppressor that interacts with the eleven-nineteen lysine-rich leukemia (ELL) protein to inhibit cancer progression of B-cell lymphoma, prostatic cancer and hepatocellular carcinoma( Pascal et al, 2019 ; Xiao et al, 2008 ). MFSD9 encodes a transport protein, but its function in cancer has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have identified RORA as a novel candidate gene for ASD, which may be conducive to the known pathophysiology, behaviors, and sex bias of ASD ( 34 ). ELL Associated Factor 1 (EAF1) is one of the EAF family members, which plays an essential role in tumor suppression and embryogenesis ( 35 ). EAF1 and EAF2 can suppress Wnt/β-catenin signaling to affect neuroectodermal and mesodermal patterning ( 36 ).…”
Section: Discussionmentioning
confidence: 99%